PENGEMBANGAN MODUL AJAR MENULIS TEKS DESKRIPSI DENGAN MODEL DISCOVERY LEARNING PADA SISWA KELAS VII SMP NEGERI 02 PONTIANAK - Rahayu, Dian; Priyadi, Antonius Totok; Sanulita, Henny (Universitas Tanjungpura, 2024)
This study addressed the problem of many teachers lacking understanding of module structure and insufficient reference materials, leading to suboptimal educational modules. Limited media usage also caused boredom and low learning outcomes. The study aimed to develop an educational module, assess its feasibility, test media effectiveness, and determine the module